Efforts of SMP Muhammadiyah 5 Reinforcement in Improving Learning Activities During the Covid-19 Pandemic - Intan Rahma Febriani; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This research is to find out how online learning is during the Covid-19 pandemic at SMP 5 Muhammadiyah Tulangan. The research method used is a descriptive qualitative method that will describe the research results. The method of data collection was done by conducting interviews with the teachers who teach at the school. The approach used in this research is ethnography and phenomenology to find out directly the efforts made to improve the results of learning activities. In order to continue to provide good education, the teachers at SMP Muhammadiyah 5 Tulangan are trying to understand the problems of online learning, especially during the Covid-19 outbreak. Several attempts were made to improve student learning activities. The results of this study found that there were two kinds of efforts, namely online learning with creative teaching methods and offline learning with a capacity of 50%. Understanding the material provided by the teacher can be accessed in face-to-face learning which is limited to 50%. Thus, learning activities during COVID-19 can take place as fully and effectively as possible by making maximum efforts to make the efforts that have been made.